HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHIC ANALYSIS OF ASPARTAME AND SODIUM SACCHARIN IN FOODS - Yilmaz, Muharrem; Afsar, Huseyin (YILDIZ TECHNICAL UNIV, 2012)
In this study, the qualitative and quantitative analyses of aspartame and saccharin investigated using Instrumental High Performance Thin-Layer Chromatography (HPTLC). Aspartame developed on HPTLC Silica Gel 60 plates, then quantified at 620 nm after derivitization with ninhydrine solution. The aspartam calibration plot was linear between 200 and 1200 ng/spot with a coefficient of determination (R-2) of 0.9955. When 10 repetition of 500 ng/spot aspartame processed, results were found between 95,7-107,4 %. The limits of detection (LOD) and quantification (LOQ) were 36.73 and 111.31 ng/spot, respectively. % Recovery was found between 95.0 and 96.6 with different type of matrixes such as sugar syrup, flour, infant food and chocolate with sugar. Then the plate immersed to zinc nitrate solution to get stable and marked aspartame spot. % Recovery was determined between 96.5 and 103.0, and LOD and LOQ were 5.42 and 16.44 ng/spot, respectively at this condition. Sodium saccharin developed on HPTLC Silica Gel 60 F254 plates, then quantifed at 230 nm. The saccharin calibration plot was linear between 200 and 1200 ng/spot with a coefficient of determination (R-2) of 0.9974. When 10 repetition of 500 ng/spot aspartam processed, results were found between 96.5-102.7 %. LOD and LOQ were 8.81 and 26.68 ng/spot, respectively. % Recovery was found between 99.1 and 107.7 with different types of matrix.
Keywords: HPTLC; aspartame; sodium saccharin; foods; Engineering